Knockout of the sugar transporter OsSTP15 enhances grain yield by improving tiller number due to increased sugar content in the shoot base of rice (Oryza sativa L.) - Li, Mingjuan; Li, Hongye; Zhu, Qidong; Liu, Dong; Li, Zhen; Chen, Haifei; Luo, Jinsong; Gong, Pan; Ismail, Abdelbagi M.; Zhang, Zhenhua (Wiley, 2024)
Sugar transporter proteins (STPs) play critical roles in regulating plant stress tolerance, growth, and development. However, the role of STPs in regulating crop yield is poorly understood. This study elucidates the mechanism by which knockout of the sugar transporter OsSTP15 enhances grain yield via increasing the tiller number in rice. We found that OsSTP15 is specifically expressed in the shoot base and vascular bundle sheath of seedlings and encodes a plasma membrane‐localized high‐affinity glucose efflux transporter. OsSTP15 knockout enhanced sucrose and trehalose‐6‐phosphate (Tre6P) synthesis in leaves and improved sucrose transport to the shoot base by inducing the expression of sucrose transporters. Higher glucose, sucrose, and Tre6P contents were observed at the shoot base of stp15 plants. Transcriptome and metabolome analyses of the shoot base demonstrated that OsSTP15 knockout upregulated the expression of cytokinin (CK) synthesis‐ and signaling pathway‐related genes and increased CK levels. These findings suggest that OsSTP15 knockout represses glucose export from the cytoplasm and simultaneously enhances sugar transport from source leaves to the shoot base by promoting the synthesis of sucrose and Tre6P in leaves. Subsequent accumulation of glucose, sucrose, and Tre6P in the shoot base promotes tillering by stimulating the CK signaling pathway.Sugar transporter proteins (STPs) play critical roles in regulating plant stress tolerance, growth, and development. However, the role of STPs in regulating crop yield is poorly understood.This study elucidates the mechanism by which knockout of the sugar transporter OsSTP15 enhances grain yield via increasing the tiller number in rice.We found that OsSTP15 is specifically expressed in the shoot base and vascular bundle sheath of seedlings and encodes a plasma membrane‐localized high‐affinity glucose efflux transporter. OsSTP15 knockout enhanced sucrose and trehalose‐6‐phosphate (Tre6P) synthesis in leaves and improved sucrose transport to the shoot base by inducing the expression of sucrose transporters. Higher glucose, sucrose, and Tre6P contents were observed at the shoot base of stp15 plants. Transcriptome and metabolome analyses of the shoot base demonstrated that OsSTP15 knockout upregulated the expression of cytokinin (CK) synthesis‐ and signaling pathway‐related genes and increased CK levels.These findings suggest that OsSTP15 knockout represses glucose export from the cytoplasm and simultaneously enhances sugar transport from source leaves to the shoot base by promoting the synthesis of sucrose and Tre6P in leaves. Subsequent accumulation of glucose, sucrose, and Tre6P in the shoot base promotes tillering by stimulating the CK signaling pathway.